(untitled) (Journal of Organizational Psychology, 2017)
This study examined the outcomes and assumptions of Bauer’s (2010) model of onboarding levels (Compliance, Clarification, Culture, and Connection). Specifically, we examined the impact of onboarding levels on subsequent work attitudes (i.e., perceived utility of onboarding, organizational commitment, perceived organizational support, and job satisfaction). Participants who were onboarded at the highest level, Connection, had higher perceptions of onboarding utility, organizational commitment, perceived organizational support, and job satisfaction. Bauer’s hierarchical assumption was supported, however our data suggests the frequency of occurrence of these levels is quite different. Organizations should design onboarding programs that provide all four levels of onboarding experiences.